Synthesis, X-ray crystallography, spectroscopic characterizations, and density functional theory of the chloride-bound five-coordinate high-spin Iron(II) “Picket Fence” porphyrin complex - Feriel Salhi; Mondher Dhifet; Mondher Dhifet; Bouzid Gassoumi; Noureddine Issaoui; Noureddine Issaoui; Habib Nasri (Frontiers in Chemistry, 2025)
An Fe(II)-chlorido five-coordinate picket fence porphyrin complex with the formula [K (crypt-222)][FeII(TpivPP)Cl]·C6H5Cl (I) (where TpivPP is the picket fence porphyrin and crypt-222 is the cryptand-222) has been synthesized and characterized. Cryptand-222 was used to solubilize potassium chloride . UV/Vis and IR spectroscopic data studies have also been performed. The X-ray structural analysis indicates that the Fe(II) cation is a high-spin (S = 2) porphyrin and has the dxy2dxz1dyz1dz21dx2−y21 ground-state electronic configuration. The average equatorial iron-pyrrole N bond length (Fe__Np = 2.1091(2) Å) and the distance between the iron and the 24-atom mean plane of the porphyrin ring (Fe-PC = 0.57 Å) are similar to those of the reported five-coordinated Fe(II) high-spin (S =2) metalloporphyrins. Theoretical calculations on complex I were carried out, including (i) the optimized molecular structure using the DFT/B3LYP-D3/LanL2DZ level of theory, (ii), frontier molecular orbital (FMO) calculations, (iii) molecular electronic potential analysis (MEP), and (vi) the ELF and LOL analyses. These latter theoretical studies indicate the strong hydrogen bond linking the oxygen atom of the pivaloyl groups of the TpivPP porphyrinate and some carbon atoms of the cryptand-222.